Receptivity-based uterine fibroid surgery: an updated systematic review of the evidence - Onder Celik; Onder Koc; Arzu Yurci; Aynur Ersahin; Nilufer Celik; Fatma Tanilir; Naziye Gurkan; Ramazan Ozyurt; Mustafa Dogan Ozcil; Bulent Duran; Cihat Unlu (Clinical and Experimental Obstetrics & Gynecology)
Background: Analyzing expression patterns of receptivity genes is a minimally invasive diagnostic method to identify the underlying cause of subfertility in women with uterine fibroid with a history of implantation failure or recurrent pregnancy loss. This updated systematic review was designed to determine the molecular and genetic changes in the endometrium of women with fibroid and how myomctomy affect the outcome of spontaneous or assisted conception treatment. We also discussed the extent to which we should consider the effects of fibroids on endometrial receptivity when deciding whether or not to perform myomectomy. Methods: A total of 184 articles reached as a result of PubMed research and meeting the selection criteria, were evaluated. Of these, 28 full text articles on uterine leiomyoma and endometrium, leiomyoma and receptivity, fibroid and implantation, myomectomy and implantation, fibroid and genes, fibroid surgery and receptivity, fibroid and uterine peristalsis, fibroid and immune cell were evaluated. Results: The endometrium of subfertile women with fibroid appears to have a disease specific pattern according to the type of the fibroid. The response of the endometrium to a fibroid may vary depending on whether the fibroid is close or far from it. Leiomyomas that contribute to subfertility must be near to or in contact with the endometrium, as is the case for Types 0, 1 and 2 leiomyomas. The proximity to the endometrial cavity makes the effect of fibroid on the endometrium more pronounced. While Type 3 fibroid causes subfertility similar to submucosal fibroids, the subfertility-producing effects of Type 4 fibroids have not been clearly clarified. However, the fact that the fibroid is far from the cavity should not mean that it has no effect on the endometrium. The mechanical stress created by a Type 4 fibroid that is not connected to the endometrium may be converted into biological signal and disrupt receptivity. Data on whether myomectomy restores impaired receptivity are mostly based on clinical observations, and studies evaluating endometrial receptivity before and after myomectomy are very few. Conclusions: Analysis of receptivity genes in subfertile women with fibroid may assist the clinician in deciding whether or not to perform myomectomy. If it is determined whether fibroids affect receptivity other than their mechanical effects, the indications for myomectomy may expand or narrow.